(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2011)
Abstract When Alexander von Humboldt left Quito in June 1802 in order to undertake the rest of his Latin-American trip of exploration, he was accompanied, aside from Aimé Bonpland, by Carlos Montúfar all the way back to Europe, including the attempt to scale the Chimborazo. Up to shortly before the city of Cajamarca in today’s Peru, Montúfar wrote an relatively unknown diary account of their travels. After a brief excursion into the life of Humboldt’s companion, the question is considered whether his diary sheds a different light on Humboldt and specifically on the mountain climb. That amounts to a comparison of the diaries of the two travel companions and to an attempt to explain the apparent contradictions. Zusammenfassung Als Alexander von Humboldt im Juni 1802 von Quito aus zum Rest seiner lateinamerikanischen Forschungsreise aufbrach, begleitete ihn, abgesehen von Aimé Bonpland, Carlos Montúfar bis nach Europa zurück begleitet, u.a. auch auf beim Versuch, den Chimborazo zu ersteigen. Bis kurz vor der Stadt Cajamarca im heutigen Peru schrieb Montúfar ein relativ unbekanntes Tagebuch zur Reise. Nach einem kurzen Ausflug in das Leben von Humboldts Begleiter steht im Zentrum der weiteren Ausführungen die Frage, ob sein Tagebuch ein anderes Licht auf Humboldt und speziell auf den Aufstiegsversuch wirft. Das läuft auf einen Vergleich der Tagebücher der beiden Reisegefährten hinaus und auf den Versuch, die scheinbaren Widersprüche aufzulösen. Resumen Cuando Alexander von Humboldt salió de Quito en junio de 1802 para continuar con el resto de su viaje de exploración por la América Latina, fue acompañado por Carlos Montúfar además de Aimé Bonpland hasta que volvieron a Europa. Este trayecto incluía la tentativa de llegar a la cima del Chimborazo. Hasta un poco antes de la cuidad de Cajamarca que está en el Perú de hoy día, Montúfar mantenía un diario relativamente no conocido del viaje. Después de una breve excursión por la vida del compañero de Humboldt, el artículo actual trata la pregunta de si su diario presenta a Humboldt bajo un aspecto diferente. Termina con una comparación de los diarios de estos dos compañeros de viaje y con explicar las aparentes contradicciones.